Radiolucencies Associated with the Second Molar Adjacent to the Impacted Third Molar in the Maxilla in Comparison to the Mandible - Maria Jabbar; Muhammad Aman; Maidah Aziz; Hira Butt; Nayab Rauf; Khadija Amjad (Gandhara University, 2023)
OBJECTIVES To find the frequency radiolucencies associated with the second molar adjacent to an impacted third molar in the maxilla as compared to the mandible. METHODOLOGY A cross-sectional descriptive study was conducted on 385 Orthopantomograms (OPG) of patients visiting Sharif Medical and Dental College (SMDC), Services Institute of Medical Sciences (SIMS) and Institute of Dentistry, CMH, Lahore Medical College, Lahore over a period of three months from December 2020 to February 2021. Patients above the age of 21 years were included in this study. Grossly carious third molars with inadequate tooth structure to be evaluated and patients with missing maxillary and mandibular third molars were excluded from the study. RESULTS The association between periapical radiolucencies (p=0.140), pericoronal radiolucencies (p=1.000) and external root resorption (p= 0.157) with the arch type (mandible/ maxilla) were not statistically significant but that of caries with the arch was significant (p≤0.001). CONCLUSION The periapical and pericoronal radiolucencies, caries and external root resorption associated with the second molar in the presence of an impacted third molar were higher in the mandible as compared to the maxilla.